KARAKTERISTIK SOSIAL BUDAYA DAN EKONOMI NELAYAN KECIL DI WILAYAH PESISIR DESA PUGER WETAN KECAMATAN PUGER KABUPATEN JEMBER - Khoirotul Fitriyah; Djoko Widodo (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2016)
This study was conducted to describe the characteristics culture social and fisherman average economics in costal areas Puger Wetan Kecamatan Puger Kabupaten Jember. The method to determine the location of the research using purposive area is coastal areas Puger Wetan Kecamatan Puger Kabupaten Jember. While Informant study using purposive method, the key informants of this study is a small fishing village in the coastal region Puger Wetan, while informants in this study support the wives of key informants and village. Data collection methods used consisted of interviews, observation, and documents. Analysis of the data used is data reduction, data presentation, and data verification. Mechanical checking the data in this study using triangulation techniques. The results showed that the tiny fishing village of Puger Wetan has its own characteristics that distinguish the fishing conditions in general. Analysis of the characteristics seen from three aspects, the social, cultural and economic. Social conditions include the participation of fishermen in a social organization. Cultural characteristics include the use of technological tools used in fishing activities, and a descendant of a family of fishermen. Economic conditions include income, expenditure, living conditions, health, and education of children